Decreased incidence of venous thromboembolism found in trauma patients with positive blood alcohol concentration on admission. (2nd January 2019) - Grigorian, Areg; Gambhir, Sahil; Al-Khouja, Lutfi; Gabriel, Viktor; Schubl, Sebastian D.; Nastanski, Frank; Lekawa, Michael; Joe, Victor; Nahmias, Jeffry
ABSTRACT: Background : The reported incidence of venous thromboembolism (VTE) disease in trauma is 1–58% and is considered a preventable cause of mortality. Positive blood alcohol concentration (BAC) is found in 8–45% of trauma admissions; however, its association with VTE is controversial. Objectives : We hypothesized that a positive BAC on admission would be associated with a lower rate of VTE in a large national database of trauma patients. Methods : We queried the largest United States trauma registry, National Trauma Data Bank (2007–2015), for any patient with positive BAC on admission. The primary outcome was VTE and the secondary outcome was mortality. A multivariable logistic regression model was used for analysis. Results : From 2, 725, 032 patients (70.1% male, 29.9% female), 1, 800, 216 (66.1%) had a negative BAC while 924, 816 (33.9%) had a positive BAC. A positive BAC was associated with lower rates of VTE (OR = 0.88, CI = 0.86–0.90, p  < 0.001) and mortality (OR = 0.91, CI = 0.90–0.93, p  < 0.001). Conclusion : In a large national database, trauma patients with a positive BAC were associated with a lower rate of VTE compared to those with negative BAC. Additionally, trauma patients with positive BAC had a lower association with mortality. These findings remained after adjustment of well-known risk factors for VTE and mortality, respectively.